Optimasi Penambahan Transformator Sisipan Terhadap Keandalan Jaringan di Gardu Distribusi - Hendrawan Riki Prabowo; Arief Marwanto (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2025)
Distribution substations are one of the important assets managed by the State Electricity Company (PLN), especially distribution transformers to distribute electric power to consumers. The MOADK006 Distribution Substation is located in Wakarleli Village, Moa District, Southwest Maluku Regency, Maluku Province with a transformer capacity of 100 kVA which is supplied by the Inner City Feeder of the PLN Moa electricity system. The transformer experiences a load condition exceeding 80% of its capacity. To overcome the problem of overloading at the MOADK006 distribution substation, which reached 93.72% of the 100 kVA capacity, it has exceeded the standards set by PLN ED Decree No.0017.E/DIR/2014. As a solution, an insert transformer with a capacity of 100 kVA was added. After adding the insert transformer, the MOADK006 distribution substation load was reduced to 45.02%, while the insert transformer bore a load of 48.81%. With this load distribution, the two distribution substations are in good loading condition, namely less than 60%, in accordance with the guidelines of PLN ED Decree No.0017.E/DIR/2014. It is estimated that the MOADK006 distribution substation can last up to 8 years. The voltage measurement at the end of the network after adding the insert transformer also experienced improvements, where the results of the Drop Voltage value at the end of the network before and after adding the insert transformer were 8.88% to 2.70% for the R phase, 7.59% to 3.16% for the S phase, and 7.55% to 2.25% for the T phase. Thus, the addition of the insert transformer proved to be effective in reducing the load on the distribution substation. MOADK006 and improves the voltage value at the end of the network, so that it meets applicable operational standards.